Blood-Based Indicators of Insulin Resistance and Metabolic Syndrome in Bottlenose Dolphins (Tursiops truncatus) - Venn-Watson, Stephanie; Smith, Cynthia R.; Stevenson, Sacha; Parry, Celeste; Daniels, Risa; Jensen, Eric; Cendejas, Veronica; Balmer, Brian; Janech, Michael; Neely, Bejamin A.; Wells, Randall (Frontiers in Endocrinology, 2013)
Similar to people with metabolic syndrome, bottlenose dolphins (Tursiops truncatus) can have a sustained postprandial hyperglycemia and hyperinsulinemia, dyslipidemia, and fatty liver disease. A panel of potential postprandial blood-based indicators of insulin resistance and metabolic syndrome were compared among 34 managed collection dolphins in San Diego Bay, California (Group A) and 16 wild, free-ranging dolphins in Sarasota Bay, Florida (Group B). Compared to Group B, Group A had higher insulin (2.1 ± 2.5 and 13 ± 13 µIU/ml), glucose (87 ± 19 and 108 ± 12 mg/dl) and triglycerides (75 ± 28 and 128 ± 45 mg/dl) as well as higher cholesterol (total, high density lipoprotein cholesterol, and very low density lipoprotein cholesterol), iron, transferrin saturation, gamma-glutamyl transpeptidase (GGT), alanine transaminase, and uric acid. Group A had higher percent unmodified adiponectin. While Group A dolphins were older, the same blood-based differences remained when controlling for age. There were no differences in body mass index (BMI) between the groups, and comparisons between Group B and Group A dolphins have consistently demonstrated lower stress hormones levels in Group A. Group A dolphins with high insulin (greater than 14 µIU/ml) had higher glucose, iron, GGT, and BMI compared to Group A dolphins with lower insulin. These findings support that some dolphin groups may be more susceptible to insulin resistance compared to others, and primary risk factors are not likely age, BMI, or stress. Lower high-molecular weight adiponectin has been identified as an independent risk factor for type 2 diabetes in humans and may be a target for preventing insulin resistance in dolphins. Future investigations with these two dolphin populations, including dietary and feeding differences, may provide valuable insight for preventing and treating insulin resistance in humans.